Essential oils against gastrointestinal nematodes in sheep in vitro and chemical composition of those plants - Osório, Thaís Moreira (2023)
The present study aimed to evaluate the in vitro potential of aromatic plants Aloysia triphylla (cidró ou erva-luísa), Corymbia citriodora (eucalipto-limão), Lippia alba (falsa-melissa) e Piper gaudichaudianum (pariparoba), in helminths eggs and larvae, determine their main constituents. For this, the essential oils (OEs) of the plants were extracted from leafs, in the clevenger apparatus and to determine the main constituents was carried out the gas chromatography coupled to mass spectrometry. The Egg eclodibility assay (EEA) and Larval development test (DLT) were performed using essential oils at concentrations ranged from 75 at 0.2%. mg.mL, and all tests followed by commercial anthelmintic positive control and negative control distilled water. For EEA, A. triphylla e L. alba OEs demonstred equivalente efficacy to the commercial drug at all concentrations that was tested, while P. gaudichaudianum OE demonstred equivalente efficacy at 15 mg/mL and the C. citriodora OE at 10 mg/mL. About DLT, all concentratios of the studied essential oils were effective as the comercial drug results in this test. The dominant constituent in OEs were: geraniale (A. triphylla), citronellal (L. alba), linalool (L. alba) and α-humuleno (P. gaudichaudianum). Based on the results presented here, the OEs present potential for use as natural anthelmintics for the treatment of endoparasitosis in sheep.